Athlete’s Passport: Prevention of Infections, Inflammations, Injuries and Cardiovascular Diseases - Mennitti, Cristina (J Clin Med, 2020)
Laboratory medicine in sports medicine is taking on an ever-greater role in the assessment and monitoring of an athlete’s health condition. The acute or intense exercise practiced by elite athletes can lead to the appearance of infections, inflammations, muscle injuries or cardiovascular disorders, whose diagnosis is not always rapid and efficient, as there is no continuous monitoring of the athlete. The absence of such monitoring can have serious consequences in terms of recovery of the professional athlete. These imbalances can induce metabolic adaptations which translate into alterations of specific parameters in terms of concentration and activity. The aim of this study was to follow the variation of specific biochemical biomarkers in a basketball team participating to the maximum championship during different phases of the agonistic season. The evaluation of serum biomarkers can help doctors to safeguard the athlete’s health and sports trainers to adapt workouts, thus avoiding the appearance of diseases and injuries that in some cases can be underestimated by becoming irreversible ailments that do not allow the athlete to return to a healthy state. This information can be useful to create athlete biologic passports.